1987
DOI: 10.1161/01.res.61.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Porcine coronary arteries with regenerated endothelium have a reduced endothelium-dependent responsiveness to aggregating platelets and serotonin.

Abstract: To test the ability of regenerated endothelium to evoke endothelium-dependent relaxations, male Yorkshire pigs underwent balloon endothelial denudation of the proximal left anterior descending coronary artery. Endothelium-dependent responses were examined in vitro, in rings of coronary segments taken from the denuded area or from the proximal left circumflex coronary artery. The experiments were performed 8 days or 4 weeks after the denudation. Endothelial regrowth was confirmed by histologic examination 8 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
139
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(153 citation statements)
references
References 38 publications
13
139
1
Order By: Relevance
“…Attempts have been made to clarify this hyperresponsiveness of arteriosclerotic vessels by experiments in vitro, but the results differed greatly depending on species and experimental conditions (Henry & Yokoyama, 1980;Godfraind & Miller, 1983;Kawachi et al, 1984;j / Ginsburg et al, 1984;Harrison et al, 1987). The defective endothelium-derived relaxing factor (EDRF) release in atherosclerotic vessels (Freiman et al, 1986;Jayakody et al, 1987a; (EDCF) or endothelin (Yanagisawa et al, 1988) as is found in hypertension or in regenerating endothelium (Luescher & Vanhoutte, 1986;Vanhoutte, 1987;Shimokawa et al, 1987 (Hof et al, 1987), for this purpose. The calcium after (continuous line) antagonist shifted the dose-response curves to NA cg 1. n = 6 for each and Phen (but not AII) more effectively to the right in atherosclerotic animals so that the pressor In summary, our experiments support the view that pressor effects of several vasoconstrictor agents are enhanced in atherosclerotic animals.…”
Section: Conscious Rabbitsmentioning
confidence: 99%
“…Attempts have been made to clarify this hyperresponsiveness of arteriosclerotic vessels by experiments in vitro, but the results differed greatly depending on species and experimental conditions (Henry & Yokoyama, 1980;Godfraind & Miller, 1983;Kawachi et al, 1984;j / Ginsburg et al, 1984;Harrison et al, 1987). The defective endothelium-derived relaxing factor (EDRF) release in atherosclerotic vessels (Freiman et al, 1986;Jayakody et al, 1987a; (EDCF) or endothelin (Yanagisawa et al, 1988) as is found in hypertension or in regenerating endothelium (Luescher & Vanhoutte, 1986;Vanhoutte, 1987;Shimokawa et al, 1987 (Hof et al, 1987), for this purpose. The calcium after (continuous line) antagonist shifted the dose-response curves to NA cg 1. n = 6 for each and Phen (but not AII) more effectively to the right in atherosclerotic animals so that the pressor In summary, our experiments support the view that pressor effects of several vasoconstrictor agents are enhanced in atherosclerotic animals.…”
Section: Conscious Rabbitsmentioning
confidence: 99%
“…Shimokawa et al 23 reported that PAF caused endothelium-dependent relaxation in isolated porcine coronary arteries at concentrations several orders of magnitude higher (IC 50 10 Ϫ4.5 mol) than used in the present study. Hu and Man 22 reported a weak biphasic response after PAF injection in an isolated rat heart preparation perfused with Krebs-Henseleit buffer.…”
mentioning
confidence: 58%
“…28 A direct vasodilator effect on coronary arterial vessels has been demonstrated at PAF concentrations several orders of magnitude higher than those achieved in the present study. 23,27 Although statistically significant, the magnitude of PAF-induced collateral vasodilation during thromboxane A 2 receptor blockade was small.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…49 The repaired endothelial lining is however markedly dysfunctional in part due to the arterial pressure that the vein is now subjected to. 50,51 After implantation, the vein graft, which has been subjected only to an internal pressure of 10 mm Hg in the venous circulation, is immediately subjected to the arterial pressure (100 mm Hg) as well as immediate increases in flow, longitudinal wall (shear) stress, circumferential, radial and pulsatile deformation and stress. 52 Numerous genes are upregulated in response to the altered shear stress, including adhesion molecules, 53,54 and therefore this is a substantial promoter of intimal thickening.…”
Section: Pathogenesis Of Vein Graft Diseasementioning
confidence: 99%